Coexistence of fluorescent Escherichia coli strains in millifluidic droplet reactors. Issue 8 (22nd March 2021) - Zhao, Xinne; Illing, Rico; Ruelens, Philip; Bachmann, Michael; Cuniberti, Gianaurelio; de Visser, J. Arjan G. M.; Baraban, Larysa
Abstract : We use a millifluidic system to study the multi-species bacterial growth to unveil the details of cooperation between two Escherichia coli strains inside droplet reactors. This system also has the potential for studies of drug resistance transfer. Abstract : Understanding competition and cooperation within microbiota is of high fundamental and clinical importance, helping to comprehend species' evolution and biodiversity. We co-encapsulated and cultured two isogenic Escherichia coli strains expressing blue (BFP) and yellow (YFP) fluorescent proteins into numerous emulsion droplets and quantified their growth by employing fluorescence measurements. To characterize and compare the bacterial growth kinetics and behavior in mono and co-culture, we compared the experimental observations with predictions from a simple growth model. Varying the initial ratio ( R 0 ) of both cell types injected, we observed a broad landscape from competition to cooperation between both strains in their confined microenvironments depending on start frequency: from a nearly symmetric situation at R 0 = 1, up to the domination of one subpopulation when R 0 ≫ 1 (or R 0 ≪ 1). Due to competition between the strains, their doubling times and final biomass ratios ( R 1 ) continuously deviate from the monoculture behavior. The correlation map of the two strains' doubling times reveals that the R 0 is one of the critical parameters affecting the competitive interaction between isogenic bacterial strains. Thanks to this strategy, different species of bacteria can be monitored simultaneously in real-time. Further advantages include high statistical output, unaffected bacteria growth, and long-time measurements in a well-mixed environment. We expect that the millifluidic droplet-based reactor can be utilized for practical clinical applications, such as bacterial antibiotic resistance and enzyme reaction kinetics studies.